Significant Impact of Successive On-Job Trainings on Performance of Technical Employee in Biotech Industry - Kumar, Amit; Singh, Sudhir Kumar; Kumar, Govinder (Journal of Training and Development, 2019)
Training is essential to the growth and economic well-being of industry and technical employees are main key of any Biotech Industry. Therefore training is required to nourish employee skills of all level in any organization. There are two possible ways to train the industrial employees through on-job training i.e. common for all employees and specific for work oriented at their work place. In this study, we performed five task specific on-job trainings by trainers acquainted with theoretical, practical and demonstration skills. In other words, the training is one of the most pervasive methods for enhancing individual knowledge, skills, ability and attitude as well as improving job performance in the work environment. The current study designed only five On-job training programs and the successive On-job trainings performed in upcoming continuous three years from 2016 to 2018. Training effectiveness must cause behaviour change i.e. skill transfer for job performance, thereby resulting in organizational performance. The results of this study shows that on-job training is strongly and positively affects the technical employee in terms of result oriented, target achievement and improvement in their work quality.